Application of the online teaching model based on BOPPPS virtual simulation platform in preventive medicine undergraduate experiment - Cai-Yun Chen; Xiu-Wen Shi; Shu-Ying Yin; Nai-Yuan Fan; Tian-Yuan Zhang; Xue-Ning Zhang; Chang-Ting Yin; Wei Mi (BMC Medical Education)
Abstract Background As online teaching gains prevalence in higher education, traditional face-to-face methods are encountering limitations in meeting the demands of medical ethics, the availability of experimental resources, and essential experimental conditions. Consequently, under the guidance of the BOPPPS (bridge-in, objective, preassessment, participatory learning, postassessment, summary) teaching model, the application of virtual simulation platform has become a new trend. The purpose of this study is to explore the effect of BOPPPS combined with virtual simulation experimental teaching on students’ scores and the evaluation of students’ participation, performance and teachers’ self-efficacy in preventive medicine experiment. Methods Students from Class 1 and Class 2 of 2019 preventive medicine major in Binzhou Medical University were selected as the research objects. The experimental group (class 2) (n = 51) received the teaching mode combined with BOPPPS and virtual simulation platform, while the control group (class 1) (n = 49) received the traditional experimental teaching method. After class, the experimental report scores, virtual simulation scores, students’ engagement scale (SES), Biggs questionnaires, and teachers’ sense of self-efficacy (TSES) questionnaires were analyzed. Results The experimental report results demonstrated a significant increase in the total score of the experimental group and the scores of each of the four individual experiments compared to the control group (P < 0.05). To investigate the impact of the new teaching model on students’ learning attitudes and patterns, as well as to evaluate teachers’ self-efficacy, a questionnaire survey was administered following the course. The SES results showed that students in the experimental group had high performance scores on the two dimensions of learning methods and learning emotions (t = 2.476, t = 2.177; P = 0.015, P = 0.032). Furthermore, in the Biggs questionnaire, the total deep learning score of the experimental group was higher than that of the control group (t = 2.553, P = 0.012), and the deep learning motivation score of the experimental group was higher than that of the control group (t = 2.598, P = 0.011). The TSES questionnaire shows that most teachers think it is easier to manage students and the classroom and easier to implement teaching strategies under this mode. Conclusions The combination of BOPPPS and the virtual simulation platform effectively enhances the experimental environment for students, thereby improving their academic performance, engagement and learning approach in preventive medicine laboratory courses.